Emotional Representation and Moral Framing of Indonesia’s Defeat in Al-Jazeera Arabic News: A Faircloughian Critical Discourse Analysis - Muhammad Fadhlurrahman Zakaria; Cahya Buana; Umi Kulsum (Middle Eastern Culture & Religion Issues, 2026)
This study examines how an Al-Jazeera Arabic news text constructs Indonesia’s defeat to Iraq in the fourth qualifying round of the 2026 FIFA World Cup through patterns of emotional representation and moral framing. The study aims to identify how linguistic choices and discursive strategies shape the representation of Indonesian players’ post-match conduct. This research employs a qualitative descriptive approach and is designed as a single-text critical case study. The data consists of selected excerpts from one Al-Jazeera Arabic online news article reporting the incident. The analysis was conducted through close reading using Norman Fairclough’s three-dimensional Critical Discourse Analysis framework, encompassing text analysis, discourse practice, and sociocultural practice. The findings indicate that the report constructs the Indonesian national team through evaluative lexical choices, plural categorization, causality, and imperative headline structure that foreground emotional instability, indiscipline, and collective attribution. Rather than functioning solely as neutral sports reporting, the text may be interpreted as directing readers toward a moral evaluation of the team’s conduct. This study contributes specifically to the discussion of Arab media representation of non-Arab actors in the context of sport, while also extending the application of Critical Discourse Analysis to contemporary sports journalism.